Botulinum toxin type A: basic pharmacological profile and therapeutic applications - Drinovac Vlah, Višnja; Bach-Rojecky, Lidija (Archives of Pharmacy, 2020)
Botulinum toxin Type A (BoNT/A), produced by the Gram-positive anaerobic bacteria Clostridium botulinum, is one of the most potent toxins in nature, and a very useful therapeutic tool for combating various neurological and autonomic disorders. The main pharmacological features of BoNT/A are neurospecificity, long-lasting effect, and safety. These features are grounded on its peculiar molecular mechanism of action: after specific binding to the neuronal membrane, it is internalized into the neuronal cytosol, where it specifically cleaves one of the proteins necessary for neurotransmitters release. The consequent reversible neuroparalysis lasts for several months and explains the long-lasting clinical effects after a single local toxin application. Although already approved for the prevention of chronic migraine, the basic and clinical investigations have repeatedly shown the potential of BoNT/A in relieving other chronic pain conditions. Accumulated data from experimental pain models demonstrated that BoNT/A reduces pathological pain hypersensitivity after axonal transport to the central nervous system, where it interferes with complex processes of central sensitization. Future experiments are needed to explain in more depth BoNT/A molecular mechanism of action and pharmacokinetic peculiarities.